PUNCTUATION AND PROSODY UNDER THE PERSPECTIVE OF HETEROTOPY: A LINGUISTIC AND DISCURSIVE REFLEXION ABOUT WRITING (Muitas Vozes, 2021)
The relationship between punctuation and prosody is an issue discussed by different theoretical approaches in linguistic studies. In this paper, we aim to understand this relationship under the perspective of heterotopy, formulated by Foucault (2005 [1967]). Therefore, this study assumes the idea that language is the founding heterotopy of man and of society, as defended by Corrêa (2012) in a work that investigated the production of space and spatiality in pre-university written texts. In order to exemplify this perspective, we analyze an advertisement and a school text written by a student. We hope that the analysis we assume can contribute for linguistic and discursive discussion about writing in order to characterize its constitutive heterogeneity, especially in what concerns punctuation.